Entre panelas, livros e tradições: as trajetórias de formação do professor de gastronomia - Rampim, Beatriz de Carvalho Pinto (2010)
This research looks carefully at teachers formation into the superior course of gastronomy tecnologies, a path increasingly in evidence at the brazilian educational landscape today, brings the scenery of the city of São Paulo and presents the educacional institution that first offered this type of education in the state capital: The Hotec University. The study aimed to identify key issues that constitute the process of formation of the teachers who teaches classes for this course. It is an ancient field research of practical knowledge, which used as methodological way, literature, survey data from INEP (National Institute of Educational Studies Anísio Teixeira), analysis of documents and records of the institution, interviews Story of Life with the participation of faculty, was also observed locally both in lectures and in practice. Among the basic categories, presents a formal education, non-formal education, informal education and teacher training , and how categories of support, culture, subjectivity, recognition and identity. Uses, such as bibliographic database, the theoretical foundation for the writings of Maria da Gloria Marcondes Gohn, Maurice Tardif, Michel de Certeau, Axel Honneth e Terezinha Azerêdo Rios. Narratives of the Life Story of the teachers, who teach practical and theoretical subjects for Degree in Food Technology, offered by the education institution that will take as an example, allowed the analysis and understanding of the essential elements of this professional training, as well as weight attributed by them to each item in the existing lines of trajectories and belongings. The survey noted the increasing availability of this type of education, which emerged in São Paulo in 2002. The research concludes that the professor s Degree in Food Technology covers the knowledge and experience, in times past and present, via learning the methods of formal, non formal and informal. Among aspects constituents arising from formal education, the teachers pointed out the knowledge from the technical courses, undergraduate and post graduate (specialization and strict sense) from among the constituent aspects of informal education, the teachers reported the knowledge, experience acquired through inherited knowledge, experience family, among the constituent aspects arising from non- formal education, teachers indicated the knowledge acquired through experiences with the purpose of learning, research, professional practice in the world of work and completion of courses that do not belong the formality of the school. The following subjective aspects were also identified as constituents of training: identity, composed of recognition issues, gender and culture and otherness.